The Influence of the Show and Tell Method on the Speaking Skills of Elementary School Students: A Meta-Analysis Study - Nana Supriatna; Moch Agus Sulis Setiawan (International Journal Corner of Educational Research, 2025)
This meta-analysis investigates the empirical impact of the "Show and Tell" method on the speaking skills of elementary school students. Synthesizing data from various academic libraries, books, and journals, the study aims to evaluate the method's effectiveness across primary education levels. The results reveal an overall average effect size of 2.316, placing the intervention in the "large" category. Specifically, the experimental group consistently outperformed the control group, demonstrating that the "Show and Tell" method significantly enhances oral communication proficiency. Furthermore, analysis based on grade level yielded a score of 2.46, further reinforcing its efficacy. These findings indicate that the "Show and Tell" method exerts a more substantial influence compared to traditional approaches and should be prioritized in the speaking curriculum. Consequently, this method serves as a robust pedagogical alternative for educators seeking to improve students' speaking skills through interactive and structured learning.